Kinetics and Mechanism of Oxidation of N,N-Dimethylethanolamine by Diperiodatocuprate(III) Complex in Alkaline Medium - Shan, Jinhuan; Wang, Xiaoqian; Shen, Haixia (Asian Journal of Chemistry, 2010)
The kinetics and mechanisms of the oxidation of N,N-dimethylethanolamine (DMEA) by diperiodatocuprate(III) (DPC) in aqueous alkaline medium was studied with spectrophotometry in a temperature range of 293.2-313.2 K. The reaction shows first order dependence on [DPC] and fractional order with respect to [N,N-dimethylethanolamine]. The observed rate constant (kobs) decreased with increasing [IO4–] and increased with increasing [OH–]. Increasing ionic strength of the medium decreased the rate. Free radicals were observed in the process of reaction. A mechanism involving the diperiodatocuprate(III)) as the reactive species of the oxidant has been proposed. The rate constants of the rate-determining step and the activation parameters were calculated.